Nutrition in Pediatric Inflammatory Bowel Disease: A Position Paper on Behalf of the Porto Inflammatory Bowel Disease Group of the European Society of Pediatric Gastroenterology, Hepatology and Nutrition. Issue 4 (April 2018) - Miele, Erasmo; Shamir, Raanan; Aloi, Marina; Assa, Amit; Braegger, Christian; Bronsky, Jiri; de Ridder, Lissy; Escher, Johanna C.; Hojsak, Iva; Kolaček, Sanja; Koletzko, Sibylle; Levine, Arie; et al.
ABSTRACT: Background and Aims: A growing body of evidence supports the need for detailed attention to nutrition and diet in children with inflammatory bowel disease (IBD). We aimed to define the steps in instituting dietary or nutritional management in light of the current evidence and to offer a useful and practical guide to physicians and dieticians involved in the care of pediatric IBD patients. Methods: A group of 20 experts in pediatric IBD participated in an iterative consensus process including 2 face-to-face meetings, following an open call to Nutrition Committee of the European Society of Pediatric Gastroenterology, Hepatology and Nutrition Porto, IBD Interest, and Nutrition Committee. A list of 41 predefined questions was addressed by working subgroups based on a systematic review of the literature. Results: A total of 53 formal recommendations and 47 practice points were endorsed with a consensus rate of at least 80% on the following topics: nutritional assessment; macronutrients needs; trace elements, minerals, and vitamins; nutrition as a primary therapy of pediatric IBD; probiotics and prebiotics; specific dietary restrictions; and dietary compounds and the risk of IBD. Conclusions: This position paper represents a useful guide to help the clinicians in the management of nutrition issues in children with IBD.